2001
DOI: 10.1007/s002640100225
|View full text |Cite
|
Sign up to set email alerts
|

Should the patella be replaced in total knee replacement?

Abstract: In 170 total knee arthroplasties for osteoarthritis 71 did not receive a patellar replacement (group A), while 99 knees had a cemented polyethylene patella (group B). The mean follow-up time was 36 months (30-50 months). In group A 10 patients underwent second-stage patellar resurfacing and in group B 2 knees underwent revision of the patellar component. Radiologically the average patellar congruency was similar. In both groups there were 21 non-congruent knees. In group A 8 were symptomatic and had low scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Barrack et al [12] concluded that there was an approximately equal likelihood of developing anterior knee pain post-operatively regardless of whether patellar resurfacing is done, whereas Waters and Bentley [19], Wood et al [20] and Badhe et al [21] found that the resurfaced patella performed better. Reoperations for patellofemoral problems, anterior knee pain and pain during stair climbing occurred less frequently with the resurfaced patella [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Barrack et al [12] concluded that there was an approximately equal likelihood of developing anterior knee pain post-operatively regardless of whether patellar resurfacing is done, whereas Waters and Bentley [19], Wood et al [20] and Badhe et al [21] found that the resurfaced patella performed better. Reoperations for patellofemoral problems, anterior knee pain and pain during stair climbing occurred less frequently with the resurfaced patella [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The role of patellar resurfacing has also been controversial in TKA. 1 However, prior studies have demonstrated that patellar resurfacing improves the results of TKA surgery, resulting in less pain and a lower reoperation rate. 12,21 If the patella construct is made too thick, "overstuffing" of the patellofemoral compartment will result, which theoretically may limit flexion.…”
Section: Introductionmentioning
confidence: 99%
“…That it is controversial to resurface the patella in total knee arthroplasty (TKA) remains as a topic in the literature because of the higher incidence of anterior knee pain after TKA without patellar resurfacing [1,2], which was reported to be between 5 and 47% of patients [3][4][5][6][7], and the general idea that the aetiology of anterior knee pain is related to the patellofemoral joint. Some authors recommend routinely resurfacing the patella [7][8][9][10][11], while others have reported no evidence to support routine patellar resurfacing.…”
Section: Introductionmentioning
confidence: 99%